2015
DOI: 10.1007/s10437-015-9190-y
|View full text |Cite
|
Sign up to set email alerts
|

Populations and Climatic Evolution in North Tropical Africa from the End of the Neolithic to the Dawn of the Modern Era

Abstract: At the end of the Neolithic Era, during the third millennium BCE, there were fewer humid periods, and the sub-Saharan and Sahelian zones from the Atlantic to Lake Chad assumed their current geographical form. Since then, the climate has continued undergoing major variations. The succession of climatic episodes, humid or dry, is pointed out along with the episodes' complex interactions. These variations are placed in parallel to cultural phases of evolution in archaeology and history. Climate-related events hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 74 publications
0
20
0
1
Order By: Relevance
“…It was practiced by groups of cattle keepers who seasonally cultivated cereal crops while supplementing their food supply by hunting and gathering, as evident from many Neolithic sites (Clark & Gifford‐Gonzalez, ; Mercuri, Fornaciari, Gallinaro, Vanin, & di Lernia, ; Ozainne et al, ; Sereno et al, ). Nomadic pastoralism (with full dependence on animal husbandry) appeared only after the invention of iron metallurgy and was preceded by a wide range of mixed subsistence types which included combinations of hunting, gathering, animal husbandry, and crop cultivation (Linseele, ; Maley & Vernet, ). According to this theory, the split between the current nomadic pastoralists and sedentary farmers is relatively recent and the two populations share a common ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…It was practiced by groups of cattle keepers who seasonally cultivated cereal crops while supplementing their food supply by hunting and gathering, as evident from many Neolithic sites (Clark & Gifford‐Gonzalez, ; Mercuri, Fornaciari, Gallinaro, Vanin, & di Lernia, ; Ozainne et al, ; Sereno et al, ). Nomadic pastoralism (with full dependence on animal husbandry) appeared only after the invention of iron metallurgy and was preceded by a wide range of mixed subsistence types which included combinations of hunting, gathering, animal husbandry, and crop cultivation (Linseele, ; Maley & Vernet, ). According to this theory, the split between the current nomadic pastoralists and sedentary farmers is relatively recent and the two populations share a common ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the abandonment of agricultural sites along the Niger River in large portions of Mali, Burkina Faso, Niger, and northern Benin is shown on the map of AD 1500. While Maley and Vernet (2015) have reported that climatic instabilities led to unstable flow levels in the Middle Niger River from the eighth to fifteenth centuries, and large fluctuations in the Inland Niger Delta, they suggest that these had significant consequences for regional populations and political bodies in the thirteenth to sixteenth centuries. However, Huysecom, Ozainne et al (2015) do not believe that environmental factors can be blamed for the abandonment of Seno Plain sites in the fourteenth century, and changing socio-political and economic circumstances may have played a larger role in some areas (Albert et al 2000;Champion and Fuller 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of deep-water rice (common in the Inner Niger Delta) and décrue millets or sorghum would have varied annually and inter-annually with changes in regional climate and monsoon strength (Armitage, Bristow and Drake 2015;Maley and Vernet 2015), because these would have affected not only water levels but also the physical geography of the land forms on the floodplain, particularly in the Inland Niger Delta (Jacobberger 1987;R. J. McIntosh 1983).…”
Section: Floodplain Farming With Ricementioning
confidence: 99%
“…Fine sands in the water column of Lake Yoa in northeastern Chad indicate higher wind speed and/or dune formation across the region (Francus et al, ). The remobilization of dunes (Bristow & Armitage, ), and a “slight degree” of local block elevation, constricted the meandering of the Senegal River, driving its generally fixed and incised position (i.e., Maley & Vernet, ). To the east, the discharge of the Niger reduced significantly and the Interior Delta shrank by 50% of the size it had reached during the previous humid periods (Hassan, ).…”
Section: Introductionmentioning
confidence: 99%